Impartation of Flame Retardancy to Cotton Fabric by the Application of Ammonium Magnesium Phosphate - Morteza Mostashari, Seyed; Reza Babaei Chaijan, Mohammad (Asian Journal of Chemistry, 2016)
The effect of ammonium magnesium phosphate on the flammability of cotton fabric (cotton serge, 220 g/m2) was investigated. The samples were impregnated with suitable concentrations of aqueous solutions of disodium hydrogen phosphate by means of squeeze rolls and dried in an oven at 110ºC for 30 min, then immersed and stirred in a bath of admixed solution of suitable concentrations of magnesium sulphate, ammonium chloride and aqueous solution of ammonia. The treated specimens were again squeezed rolled and dried in an oven at 110ºC for 30 min. Afterwards, they were thoroughly washed with a dilute solution of aqueous ammonia for removal of uninvited sodium sulphate formed together with ammonium magnesium phosphate and also to avoid the undesirable hydrolysis of ammonium magnesium phosphate, then the specimens were again dried at 110ºC for 30 min, cooled in a desiccator, weighed in an analytical balance and kept under ordinary conditions before the fulfillment of the vertical flame test. The optimum add-on values to impart flame and glow retardancy were about 11.97–13.9 g anhydrous ammonium magnesium phosphate per 100 g fabric. The results compile with chemical theory, coating theory and gas theory.